2015
DOI: 10.1182/blood-2014-11-610717
|View full text |Cite|
|
Sign up to set email alerts
|

EPCR-dependent PAR2 activation by the blood coagulation initiation complex regulates LPS-triggered interferon responses in mice

Abstract: Infection and inflammation are invariably associated with activation of the blood coagulation mechanism, secondary to the inflammation-induced expression of the coagulation initiator tissue factor (TF) on innate immune cells. By investigating the role of cell-surface receptors for coagulation factors in mouse endotoxemia, we found that the protein C receptor (ProcR; EPCR) was required for the normal in vivo and in vitro induction of lipopolysaccharide (LPS)-regulated gene expression. In cultured bone marrowder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 54 publications
2
92
0
Order By: Relevance
“…on May 12, 2018. by guest www.bloodjournal.org From this aPC-and fV-dependent gene signature was congruent with the LPS-induced transcriptional program that is mediated by the EPCRdependent activation of PAR2 by the ternary TF-fVIIa-fXa complex. 27 This finding indicated that the fV-sensitive aPC mechanism involved the suppression of EPCR-dependent inflammatory TF signaling. Quantitative real-time polymerase chain reaction analysis confirmed that 5A-aPC suppressed the LPS-induced expression of Peli1, Ccl22, Malt1, and Irf8 in BMDCs to the same extent as function-blocking anti-mouse TF antibodies ( Figure 3B).…”
Section: Blood 19 November 2015 X Volume 126 Number 21 Anti-inflammmentioning
confidence: 78%
See 2 more Smart Citations
“…on May 12, 2018. by guest www.bloodjournal.org From this aPC-and fV-dependent gene signature was congruent with the LPS-induced transcriptional program that is mediated by the EPCRdependent activation of PAR2 by the ternary TF-fVIIa-fXa complex. 27 This finding indicated that the fV-sensitive aPC mechanism involved the suppression of EPCR-dependent inflammatory TF signaling. Quantitative real-time polymerase chain reaction analysis confirmed that 5A-aPC suppressed the LPS-induced expression of Peli1, Ccl22, Malt1, and Irf8 in BMDCs to the same extent as function-blocking anti-mouse TF antibodies ( Figure 3B).…”
Section: Blood 19 November 2015 X Volume 126 Number 21 Anti-inflammmentioning
confidence: 78%
“…To each well, 3 mL of medium containing various reagents was added exactly as described earlier. 27 All culture media contained hirudin (2 U/mL) to inhibit potential thrombin activity.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the gene expression signature suggested that aPC and fV mediated this LPS-induced transcription program through the endothelial protein C receptor (EPCR)-dependent activation of protease-activated receptor 2 (PAR2) by the ternary tissue factor (TF)-VIIaXa complex. 7 Stabilizing the TF-VIIa-Xa complex with nematode anticoagulant protein C2 (NapC2) abolished aPC's inhibitory activity against gene expression, suggesting that aPC inhibits TF-EPCR-PAR2 by destabilizing the TF-VIIa-Xa complex. By testing several function-selective aPC variants and recombinant fV mutants, Liang et al found that inhibition of TF-EPCR-PAR2 signaling by aPC required protein S, the fV B domain, and the intact R506 cleavage site.…”
mentioning
confidence: 99%
“…They elegantly showed that ATF4 regulates the expression and secretion of angiopoietin-like 3 (Angptl3) in endothelial and stroma cells, which plays pivotal roles in supporting stemness in LT-HSCs. 7,8 LT-…”
mentioning
confidence: 99%